1 Answers

# Solve the following equation: 2/(2r – 1) – 5/3 = 1/(r + 2)

Latest posts by Admin (see all)

**Solve the following equation: 2/(2r – 1) – 5/3 = 1/(r + 2)**

**(-1, 5/2)****(1, -5/2)****(5/2, 1)****(2, 1)**

**QUICK ANSWER…**

**B**

**DETAILS…**

**Factorizing, we think of two numbers that on multiplying gives 10 (5 ****×**** 2), and on adding gives 3. The numbers are 5 and 2. Thus:**

**2r****²**** + 3r – 5 = 0**

**2r****²**** + 5r – 2r – 5 = 0**

**(2r****²**** + 5r) – 1(2r + 5)= 0**

**r(2r + 5) – 1(2r + 5)= 0**

**(r – 1)(2r + 5) = 0**

**Thus, r – 1 = 0**

**Or 2r + 5 = 0**

**r = 1 or -5/2**

**Now for the right answer to the above question:**

**Option A is incorrect.****Option B is correct.****C is not correct.****D is not the correct answer.**

**KEY-POINTS…**

**You may please note these/this:**

**Collecting like terms and resolving by LCM will lead to a quadratic equation.****Solving the quadratic equation gives the answer.**

**If you love our answers, you can simply join our community and also provide answers like this, fellow learners like you will appreciate it.**

**/ culled from 20****21**** JAMB-UTME**** MATHEMATICS**** question**** 1 ****/**